Analysis of Genetic Diversity in the Traditional Chinese Medicine Plant ‘Kushen’ (Sophora flavescens Ait.) - Schultz, Carolyn J.; Goonetilleke, Shashi N.; Liang, Jianping; Lahnstein, Jelle; Levin, Kara A.; Bianco-Miotto, Tina; Burton, Rachel A.; Mather, Diane E.; Chalmers, Kenneth J. (Frontiers in Plant Science, 2021)
Kushen root, from the woody legume Sophora flavescens, is a traditional Chinese medicine that is a key ingredient in several promising cancer treatments. This activity is attributed in part to two quinolizidine alkaloids (QA), oxymatrine and matrine, that have a variety of therapeutic activities in vitro. Genetic selection is needed to adapt S. flavescens for cultivation and to improve productivity and product quality. Genetic diversity of S. flavescens was investigated using genotyping-by-sequencing on 85 plants grown from seed collected from 9 provinces of China. DArTSeq provided over 1000 single nucleotide polymorphism (SNP) markers that were used in phylogenetic analysis to reveal clear regional differences for S. flavescens. One accession from each region was selected for PCR-sequencing to identify gene-specific SNPs in the first two QA pathway genes, lysine decarboxylase (LDC) and copper amine oxidase (CAO). To obtain SfCAO sequence for primer design we used a targeted transcript capture and assembly strategy using publicly available RNA sequencing data. Partial gene sequence analysis of SfCAO revealed two recently duplicated genes, SfCAO1 and SfCAO2, in contrast to the single gene found in the QA-producing legume Lupinus angustifolius. We demonstrate high efficiency converting SNPs to KASP markers developing 27 new KASP markers, 17 from DArTSeq data, 7 for SfLDC and 3 for SfCAO1. To complement this genetic diversity analysis a field trial site has been established in South Australia, providing access to diverse S. flavescens material for morphological, transcriptomic and QA metabolite analysis. Analysis of dissected flower buds revealed that anthesis occurs before buds fully open suggesting a potential for S. flavescens to be an inbreeding species, however this is not supported by the relatively high level of heterozygosity observed. Two plants from the field trial site were analysed by quantitative real-time PCR and levels of matrine and oxymatrine were assessed in a variety of tissues. We are now in a strong position to select diverse plants for crosses to accelerate the process of genetic selection needed to adapt kushen to cultivation and improve productivity and product quality.